PREVALENCE OF THE BACTERIAL FLORA IN THE ORAL CAVITY OF DIABETIC INDIVIDUALS IN PONDICHERRY - M. LYDIA RAJAKUMARI; P. SARAVANA KUMARI (International Journal of Pharma and Bio Sciences, 2016)
Our aim is to determine the bacterial flora in the oral cavity of diabetic individuals in Pondicherry. In this study 200 buccal swabs from Diabetic individuals from age group 35±30 were included in the study. Blood Agar was used for the primary isolation of the bacterial isolates. Morphological, biochemical and phylogenetic classification were used for the identification of bacteria. Gram positive bacteria were predominant organisms in the oral cavity of diabetic individuals. Disturbances caused by the changes in the normal flora may lead to changes in the oral cavity, this may cause pathogenic micro flora to multiply and further lead to diseases. The normal flora of every individual is not same and depends on the oral hygiene. The prevalence and isolation of bacteria from the oral cavity of diabetic individuals was studied. Staphylococcus aureus and Streptococcus species were the predominant micro flora in this study.